Ultrasonic characterization of modified Cr_2O_3 coatings by reflection coefficient spectroscopy - 李继承 林莉 李喜孟 李光 雷明凯 (Transactions of Nonferrous Metals Society of China, 2010)
Pores,microcracks and density of plasma sprayed Cr2O3 coatings before and after high-intensity pulsed ion beam（HIPIB） irradiation were investigated using the ultrasonic reflection coefficient spectroscopy（URCS）.The URCS was analyzed based on an acoustic transmission model for the multi-layered structure.The longitudinal velocity in the coatings was calculated from the experimental URCS,and the attenuation coefficient expression was deduced by comparing the experimental and numerical fitting amplitude spectral lines.The longitudinal velocity of as-sprayed Cr2O3 coating is 2 002 m/s,and increases to 2 099 and 2 148 m/s after being irradiated by HIPIB with 1 and 5 shots.Correspondingly,the factor A changes from 0.046 to 0.026 and 0.020 and n from 1.702 to 1.658 and 1.649 in the attenuation coefficient expression of α=Af n.It is observed that the surface morphology of Cr2O3 coatings changes from rough and porous to smooth and uniform with the increase of shot number,which accords with the ultrasonic analyses reasonably.The URCS seems to provide a convenient and nondestructive method to characterize surface modification of the plasma sprayed coatings.